Strategi Efektif Dalam Pengajaran Muhadatsah: Meningkatkan Keterampilan Berbicara Dalam Bahasa Arab - Akmal, Muhammad; Moh. Syaifudin (JAMBURA Elementary Education Journal, 2024)
This article discusses effective strategies in the teaching of muhadatsah, i.e. speaking skills in Arabic, which are very important in the process of learning languages. In the learning of Muhadatsha, a systematic and interactive approach is required to develop the student's speech skills optimally. This article explores various teaching methods that have proven effective, such as interactive communication techniques, conversation simulation, and the use of educational technology. By analyzing the results of the implementation of this strategy, this article provides recommendations for further development in the teaching of muhadatsah. The findings suggest that these techniques not only improve students' speaking skills but also strengthen their confidence in communicating in Arabic. Therefore, the application of appropriate and innovative methods is essential to significantly improve their learning outcomes.